2021
DOI: 10.1002/pbc.29099
|View full text |Cite
|
Sign up to set email alerts
|

Decision making for hematopoietic stem cell transplantation in pediatric, adolescent, and young adult patients with a hemoglobinopathy—Shared or not?

Abstract: Background: Hematopoietic stem cell transplantation (HSCT) offers an established curative option for sickle cell disease (SCD) and thalassemia patients but is associated with significant risks. Decision making is a complex process and shared decision making (SDM) could be a fitting approach in case of such preference-sensitive decisions. This study investigated what level of SDM is used in conversations with hemoglobinopathy patients and/or their caregivers considering HSCT as a curative treatment option.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Research evaluating the SDM approach in conversations showed low or moderate levels of patientinvolving behavior. (40,41) These results shows the need for the implementation of SDM interventions and SDM training for HCP. In treatment decision-making, an advocating role of the HCP is necessary in which both the patient's health and respect for the patient's self-determination need to be thoughtfully balanced (39).…”
Section: Discussionmentioning
confidence: 92%
“…Research evaluating the SDM approach in conversations showed low or moderate levels of patientinvolving behavior. (40,41) These results shows the need for the implementation of SDM interventions and SDM training for HCP. In treatment decision-making, an advocating role of the HCP is necessary in which both the patient's health and respect for the patient's self-determination need to be thoughtfully balanced (39).…”
Section: Discussionmentioning
confidence: 92%
“…38 HSCT decision regret may relate to insu cient information about HSCT side effects provided to patients before transplantation. As the HSCT treatment decision is a "preferencesensitive" decision, 39 shared decision-making is suggested. "Limited activity space" is a subtheme that highlights a shrunken social world for HSCT survivors.…”
Section: Discussionmentioning
confidence: 99%
“…This was also observed in previous studies in other areas of medicine [ 28 ] . In our study, this may be due to a (possibly unconscious) treatment preference among paediatricians, which may have led to discussing only one option, and thereby nudging the parent/patient to choose this option [ 29 , 30 ]. Audio-recordings indicated a discrepancy between consistently applying SDM compared to advising what was considered by paediatricians as the best available treatment option.…”
Section: Discussionmentioning
confidence: 99%